Environmental Based Education: Making Nature a Learning Resource - Andryadi, Andryadi; Hidayat, Muslih; Zalnur, Muhammad; Susanti, Afrina (Al-Hashif: Jurnal Pendidikan dan Pendidikan Islam, 2025)
In education, learning resources are important in supporting the learning process to be more meaningful and contextual. One of the most extensive and natural learning resources is the universe. Nature not only provides empirical knowledge but also provides direct experiences that can shape character, increase environmental awareness, and build emotional relationships between students and the surrounding environment. This study aims to examine the use of nature or the environment as a learning resource that is relevant to educational needs in the modern era, where students are accustomed to fast and instant digital technology. This study uses a library research method by reviewing various literature, journals, books, and scientific documents related to the use of nature in learning. Based on the concept put forward by the Association for Educational Communications and Technology (AECT), there are six types of learning resources, one of which is the setting, namely the environment or context where learning takes place. In this case, nature is positioned not only as a learning setting, but also as the main source that is rich in educational values. The results of the study show that the use of nature as a learning resource makes a positive contribution to the formation of environmental awareness, strengthening character values, and increasing learning effectiveness. Thus, this research is expected to encourage the integration of nature-based learning resources into educational practices, while strengthening awareness of the importance of environmental conservation through meaningful and contextual learning activities.